Growth and Yield of Soybean (Glycine max L.) as Influenced by Phosphorus - Morshed, RM; Rahman, MM; Rahman, MA (Bangladesh Journal of Scientific and Industrial Research, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The experiment was conducted to find out the influence of phosphorus (P) on growth and yield of soybean (Glycine max L., variety: G-2). The treatments were: control (P1) and with the application of 50% (P2), 75 % (P3), 100 % (P4), 125 % (P5) and 150 % (P6) of the BARC recommended dose of P. Nitrogen, K and S were applied as blanket as per BARC recommendation. Seeds were inoculated with Bradyrhizobium inoculum before sowing. All the treatments of P application showed higher growth than that of the control. P5 treatment (11.25 kg P ha-1) showed maximum growth and yield, which was 84.73% higher than that of control. The yield changed as a parabola curve with the increase of P application. The yield component, namely number of pods plant-1, number of seeds pod-1, pod weight plant-1 and number of seed plant-1 increased with the increase of P levels up to 11.25 kg P ha-1. The application of P at 11.25 kg ha-1 (25% higher over BARC recommendation) produced the highest seed yield of soybean (7.50 g plant-1). So, for better yield of soybean in silty clay loam soil of Jahangirnagar University farm, application of P should be increased 25 % higher over BARC recommendation. Key words: Soybean, Phosphorus, Growth, Yield DOI = 10.3329/bjsir.v43i3.1151 Bangladesh J. Sci. Ind. Res. 43(3), 359-368, 2008